2016
DOI: 10.1161/hypertensionaha.116.07715
|View full text |Cite
|
Sign up to set email alerts
|

Deleting Vascular ADAM17 Sheds New Light on Hypertensive Cardiac Hypertrophy

Abstract: A disintegrin and metalloprotease (ADAM) 17 has sheddase activity for cleaving the ectodomain of several precursor molecules, including heparin-binding epidermal growth factor (EGF)-like growth factor. Over the past decade, Dr Eguchi and his colleagues have meticulously presented evidence that ADAM17 couples the angiotensin II (Ang II) type-1 (AT1) receptor to activation of the EGF receptor (EGFR) in vascular smooth muscle cells. Studies on cultured cells have shown that EGFR transactivation is responsible for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…Of course, issues such as genetic compensation with germline gene KO, potential experimental immunosuppression or preconditioning with renal transplants, and the sheer magnitude of the stress on the heart with pressure overload, could be raised to question the broad applicability of these findings. Several recent studies support the conclusion that ANG II can act independently of, or in synergy with, increased blood pressure to induce cardiac hypertrophy (27,523). Three examples are cited here.…”
Section: Ang II In Cardiac Hypertrophymentioning
confidence: 62%
See 2 more Smart Citations
“…Of course, issues such as genetic compensation with germline gene KO, potential experimental immunosuppression or preconditioning with renal transplants, and the sheer magnitude of the stress on the heart with pressure overload, could be raised to question the broad applicability of these findings. Several recent studies support the conclusion that ANG II can act independently of, or in synergy with, increased blood pressure to induce cardiac hypertrophy (27,523). Three examples are cited here.…”
Section: Ang II In Cardiac Hypertrophymentioning
confidence: 62%
“…Investigation of this model has contributed to our understanding of the relationship between the RAS, oxidative stress, and perivascular fibrosis. In young mRen2 (27) rats, an antioxidant, Tempol, prevents cardiac oxidative stress and perivascular fibrosis without altering hypertension (1144). A subsequent study also showed that low-dose MR blocker, spironolactone, attenuates perivascular fibrosis and cardiac NADPH oxidase activity, suggesting the contribution of MR activation in this model (350).…”
Section: Mineralocorticoid Receptormentioning
confidence: 91%
See 1 more Smart Citation
“…28 Thus, smooth muscle AT1 receptor function may regulate cardiac hypertrophy by intercellular signaling and paracrine factors involving the vasculature. 29…”
Section: Choose Your Modelmentioning
confidence: 99%